1999
DOI: 10.1007/bf03164905
|View full text |Cite
|
Sign up to set email alerts
|

Thallium and FDG uptake by atelectasis with bronchogenic carcinoma

Abstract: We report a case of bronchogenic carcinoma with atelectasis studied by T1-SPECT and FDG-PET. In the carcinoma, abnormally high uptake of T1 and FDG were detected, but in the region of atelectasis, an abnormally high uptake of T1 with a relatively low uptake of FDG were observed. On quantitative analyses, the T1 retention indexes of the tumor and atelectasis were 29.7 and 42.0. The mean SUVs of FDG of the tumor and the atelectasis were 8.92 and 1.28. T1-SPECT could not distinguish the atelectasis from the carci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
(2 reference statements)
0
6
0
Order By: Relevance
“…In the case described by Kawabe et al, FDG-PET was superior to thallium scanning in distinguishing between atelectasis and tumour. 26 Flores et al…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…In the case described by Kawabe et al, FDG-PET was superior to thallium scanning in distinguishing between atelectasis and tumour. 26 Flores et al…”
Section: Discussionmentioning
confidence: 89%
“…Although wash‐out of activity is typical of inflammatory atelectasis, Tl‐201 retention in atelectatic lung may be prolonged, giving a false positive result for tumour involvement in some cases. In the case described by Kawabe et al , FDG‐PET was superior to thallium scanning in distinguishing between atelectasis and tumour 26 . Flores et al reported that thallium‐201 was less sensitive and specific than CT in the imaging of lung tumours 13 .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…[43][44][45] In addition to its diagnostic value, the accurate differentiation between tumor and atelectasis achieved by PET has proved beneficial for the creation of appropriate size portals during radiation therapy planning, to minimize radiation dose to normal tissue, 46 and could potentially be useful in ensuring that selection of sites for response assessment avoids atelectatic areas. McAdams and colleagues 44 reported their results on 9 patients with rounded atelectasis who underwent dedicated FDG-PET imaging.…”
Section: Atelectasismentioning
confidence: 99%